Heteroatom Promoted Cycloadditions for Graphene. Issue 17 (25th October 2016) - Denis, Pablo A.
Abstract: Although Diels‐Alder and [2+2] cycloadditions have been performed onto graphene, defects are required to facilitate them. We report that heteroatom doping is a novel approach to promote these reactions onto graphene, by increasing reaction energies up to five times with respect to undoped graphene. The dopants introduced define the cycloaddition product. For example, Silicon facilitates [4+2] processes while Sulfur, Nitrogen and Boron give [2+2] products. Abstract : First principle calculations show that heteroatom doping can facilitate cycloaddition reactions onto graphene. The type of heteroatom included controls the cycloaddition product and reaction energy!